2019
DOI: 10.1021/acs.jpcc.8b11328
|View full text |Cite
|
Sign up to set email alerts
|

Management of Triplet Energy and Charge-Transport Properties of Hosts by CN Position Engineering

Abstract: Novel hosts strategically designed to have high triplet energy and bipolar carrier-transport features were derived by substituting carbazole and CN-modified carbazole at the ortho position of the ortho-connected biphenyl core with a CN functional group. The position of the CN unit in the biphenyl core was controlled, and the effect of the CN position on the photophysical properties and device performances of the blue phosphorescent organic light-emitting diodes (PHOLEDs) was studied. The CN substitution positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Electron transport can be plausible through dibenzofuran and the CN-modified biphenyl backbone with electron accepting ability. [21][22][23][24][25] It is expected that the management of the substitution position and interconnectionp ositionm ay control the carrier transport properties and energy levels of the hosts. The molecular design for electron transport properties was confirmed by picturing the highest-occupied molecular orbital (HOMO)a nd lowest-unoccupied molecular orbital (LUMO), based on frontier molecular orbital calculations using the B3LYP 6-31G* basis set in the Gaussian software.…”
Section: Resultsmentioning
confidence: 99%
“…Electron transport can be plausible through dibenzofuran and the CN-modified biphenyl backbone with electron accepting ability. [21][22][23][24][25] It is expected that the management of the substitution position and interconnectionp ositionm ay control the carrier transport properties and energy levels of the hosts. The molecular design for electron transport properties was confirmed by picturing the highest-occupied molecular orbital (HOMO)a nd lowest-unoccupied molecular orbital (LUMO), based on frontier molecular orbital calculations using the B3LYP 6-31G* basis set in the Gaussian software.…”
Section: Resultsmentioning
confidence: 99%
“…Ideal device performances of the blue PhOLEDs were achieved by the weakly bound exciplex host harvesting triplet excitons and stabilizing the device operation. The device data of the deep blue PhOLEDs are in Table and they were compared with other data reported in other papers . In addition, the device data of the mCBP:DBFTrz mixed host device were also added in Figure S7 and Table S3 (Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…[ 4–6 ] However, the stable host materials for blue PhOLEDs with high E T over 3.0 eV and suitable frontier molecular orbital energy levels (highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO)) are scarcely reported, because it is challenging to achieve all these parameters together. [ 24–35 ] In addition, the device lifetime of blue PhOLEDs is far inferior to that of red and green counterparts and thus the further attention is highly needed to promote the lifetime of blue PhOLEDs to replace the blue fluorescent emitters in commercial applications. [ 29–41 ] In general, many factors affect the lifetime of the blue PhOLEDs and one of the key factors is the stability of the host material.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24–35 ] In addition, the device lifetime of blue PhOLEDs is far inferior to that of red and green counterparts and thus the further attention is highly needed to promote the lifetime of blue PhOLEDs to replace the blue fluorescent emitters in commercial applications. [ 29–41 ] In general, many factors affect the lifetime of the blue PhOLEDs and one of the key factors is the stability of the host material. [ 23,29–41 ] On the other hand, it has been demonstrated that the mixed host systems are advantageous in improving the performance of PhOLEDs compared to single host systems due to balanced carrier density, broad recombination zone, and little charge leakage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation